291 IMMUNOLOGIC ASPECTS OF TUMOR GROWTH IN A RAT MODEL FOLLOWING HEMATOPOIETIC TRANSPLANTATION. (1st January 2005) - Holter, J.; Saste, V.; Anderson, S. L.; Do, S.; Lerner, M.; Brackett, D. J.; Epstein, R.
Abstract : A transplantable, DMBA induced breast cancer cell line originating in Wistar Furth (WF) rats was passed in vivo to examine its immunogenic characteristics, responsiveness to irradiation, and the effect of marrow transplantation. Transplantations were performed using marrow from isogeneic WF, allogeneic Lewis (Le), or immunized isogeneic WF rats. Methodologic system components included tumor challenge with 1 × 106 tumor cells, irradiation at a dose of 950 cGy, and infusion of 1 × 107 marrow cells obtained from donors. Nine rats treated with radiation alone died with marrow aplasia in 9 days. Rats challenged with tumor and no therapy died of tumor progression between 22 - 24 days (avg 22.66 ± 0.82, n = 15). Tumor-bearing WF rats treated with isogeneic marrow recovered marrow but died between 29-46 days (avg. 36.44 ± 3.4, n = 18) of tumor growth. WF rats transplanted with Le marrow showed full marrow, delayed tumor growth, but died of GVHD between 21-30 days (avg 26.06 ± 3.63, n = 17). A concurrent control study was carried out to evaluate the effect of administering isogeneic marrow from donors immunized with irradiated tumor cells. Donor resistance to tumor was confirmed following 8 weekly immunizations with irradiated tumor cells. Table 1 shows results of isogeneic immune marrow compared to isogenic and allogeneic grafts. Autografting resulted in minimal impact on survival and no cures, analogous to clinical trial findings. In contrast, significant tumor growth was inhibited (p ≤ .001) when allogeneic grafting was performed. However, when allogeneic transplants were performed GVHD was the major cause of death. The infusion of isogeneic marrow from immunized WF donors resulted in tumor regression without GVHD in all recipient rats ( p ≤ .002). We conclude that this model demonstrates evidence of independent graft versus tumor effects in a solid tumor setting and may be useful in exploring cellular infusion approaches to immunogenic tumors.